A Structured Decision Framework for Improving Solar PV Integration and Frequency Stability Using Kepner–Tregoe and Analytical Hierarchy Process: A Case Study of PT OEC - Hidayat, Saiful; Yudoko, Gatot (Riviera Publishing, 2026)
The increasing penetration of solar photovoltaic (PV) generation in industrial power systems provides significant opportunities for fuel reduction and sustainability improvement. However, high PV penetration also introduces operational challenges related to power variability and grid frequency stability, particularly in systems with limited inertia and spinning reserve. This study proposes a structured managerial decision framework to address solar PV integration challenges at PT OEC by combining Kepner–Tregoe (KT) problem analysis and the Analytic Hierarchy Process (AHP). Solar PV performance and grid frequency behavior were first analyzed to identify whether observed disturbances were caused by technical failure or structural system limitations. KT analysis was then applied to validate the root causes of frequency instability events. Based on the identified causes, four alternative solutions were evaluated using AHP across multiple criteria, including frequency stability improvement, PV energy yield impact, investment cost, implementation complexity, and operational maintainability. The results indicate that Battery Energy Storage System (BESS) is the most preferred strategic solution, followed by gas turbine spinning reserve optimization and PV–GT coordination procedures. Sensitivity analysis confirms that while BESS dominates under reliability-focused priorities, operational measures remain relevant under cost- and time-constrained scenarios. The study demonstrates that combining KT and AHP provides a robust decision-making framework for balancing reliability, cost, and long-term value in solar PV integration.